TLC determination of flavonoids from different cultivars of Allium cepa and Allium ascalonicum - Pobłocka-Olech Loretta; Głód Daniel; Żebrowska Maria E.; Sznitowska Małgorzata; Krauze-Baranowska Miroslawa (Acta Pharmaceutica)
This study comprises the optimization and validation of a new TLC method for determination of flavonols in the bulbs of seven cultivars of onions and shallots. Separation was performed on RP-18 plates with the solvent mixture tetrahydrofuran/water/formic acid (40+60+6, V/V/V) as a mobile phase. The method was evaluated for precision, linearity, LOD, LOQ, accuracy and robustness. Chromatographic analysis of the extracts revealed the presence of three main flavonols, quercetin, quercetin-4′-O-glucoside and quercetin-3,4′-O-diglucoside in the majority of analyzed cultivars. The content of flavonols in the analyzed extracts of onion bulbs varied from 123 (‘Exihibition’) to 1079 mg kg-1 fresh mass (fm) (‘Hybing’) in edible parts, and from 1727 (‘Hyline’) to 28949 mg kg-1 fm (‘Red Baron’) in outer scales. The bulbs of two shallot cultivars contained 209 (‘Ambition’) and 523 mg kg-1 fm (‘Matador’) of flavonols in edible parts and 5426 and 8916 mg kg-1 fm in outer scales, respectively.